Frontiers of policy and governance research in a smart city and artificial intelligence: an advanced review based on natural language processing - Dong, Liang; Liu, Yunhong (Frontiers in Sustainable Cities, 2023)
This paper is original and has not been published elsewhere in any form or language. Re-use of material (one figure) is clearly marked with reference. This paper does not involve the splitting up of a single study into several parts to increase the number of submissions and is not submitted to various journals or to one journal over time. This paper does not involve a concurrent or secondary publication.The results of this paper are presented with clarity and honesty and without fabrication, falsification, or inappropriate data manipulation.The authors of this paper adhere to discipline-specific rules for acquiring, selecting, and processing data.No data, text, or theories by others are presented as if they were the author's own. Other works are properly acknowledged. This research does not include human participants, their data, or biological material.Consent for publication (include appropriate statements) Not applicable